Synthesis of potential pharmaceutically active dihydropyrimidine-2-oxo and their 2-thio analogues - Halim, ME; Akhter, K; Hasan, M; Rahman, MM; Romman, UKR; Ahmed, MG (Bangladesh Journal of Scientific and Industrial Research, 2018)
The Biginelli one - pot three-component cyclocondensation was applied to prepare 3, 4 - dihydropyrimidin - 2 (1H) – ones from aldehydes, β-dicarbonyl compounds and urea (or thiourea) using ZnCl2 as a catalyst. The method offers several advantages including short reaction times and easy experimental work up procedures. Bangladesh J. Sci. Ind. Res.53(4), 327-332, 2018